Pembuatan Cutting Board Untuk Penyincangan Tandan Buah Segar (TBS) di Desa Sambirejo Timur, Kec Percut Sei Tuan, Kab Deli Serdang - Zulham Effendi; Muhammad Fauzan A Lubis; Muhammad Khairil; Melani Kurnia Fitri; Muhammad Alim (Yayasan Literasi Sains Indonesia, 2023)
The implementation of the Community Service Program will be carried out in East Sambirejo Village, Percut Sei Tuan District, Deli Serdang Regency for approximately 2 months. In implementing PPM, we designed an innovation in making a Cutting Board as a base for chopping FFB along with a container that functions to separate impurities in the form of sand, soil and other solid impurities. The implementation of the Community Service Program regarding Making Cutting Boards for Cutting Fresh Fruit Bunches (FFB) was carried out on Tuesday 23 August 2022. The activities carried out while carrying out the community service program were social services, social service activities in cleaning and caring for PKK parks and socialization of the use of cutting boards Socialization activities regarding the manufacture and use of Cutting Board tools. Community Service activities carried out by our group have been carried out well and received a good reception by the community. And the community is very enthusiastic about this activity and adds to their knowledge about making and using cutting boards. This community service activity is very beneficial for the community so that the community wants this activity to be carried out for a longer period of time